In Vitro Antibacterial Activity of Essential Oils From Tithonia Diversifolia Leaves and Flowers Against Ralstonia Solanacearum - Opondo, Florence; K’Owino, Isaac Odhiambo; Chepkwony, Sarah Cherono; Kosgei, Viola Jepchumba (European Journal of Applied Sciences, 2022)
Bacterial wilt disease caused by Ralstonia solanacearum is a major constraining factor in the production of tomatoes in Kenya, leading to an overreliance on synthetic pesticides. As a result, there is increased research on bio-pesticides as safer alternatives. The present study, therefore, characterized and evaluated in vitro antibacterial activity of essential oils from Tithonia diversifolia leaves and flowers against R. solanacearum. Hydrodistilled essential oils were characterized through Gas Chromatography-Mass spectrometry (GC-MS) while functional groups were confirmed using Fourier Transform Infrared Spectroscopy (FT-IR). Antibacterial activity was performed using the disc diffusion method and minimum inhibitory concentration evaluated using broth dilution. Hydrodistilled leaves of T. diversifolia yielded 0.18 + 0.08 % (v/w); 0.10 + 0.07 % w/w as compared to 0.15 + 0.09 % (v/w); 0.08 + 0.03 % w/w in the leaves . GC-MS profiling revealed the major compounds were (Z,Z,Z)-9,12,15- Octadecatrienoic acid ethyl ester(18%), palmitic acid (16%), spathulenol (12%), Cis- 9,12,15- Octadecatrienoic acid (8.14%), tetrateracontane (6%) and 1-Octen-3yl-acetate (5.22%) in the leaves ad α-linolenic acid trimethylester(33%), Z,Z Hexadecadienoic acid(26%), octadecanoic acid trimethylester (9%), palmitelaidic acid (8.49%), Germacrene D(5.45%), azelaic acid (5.02%) and caryophyllene oxide (5.00%) in the flowers. Antibacterial activity showed that T. diversifolia essential oils had mean inhibition zones of 12.61+ 0.22 mm and 11.82 + 0.76 mm from the leaves and flowers respectively, in comparison to metham sodium which gave inhibition zone of 25.78 ±0.29 mm (p = 0.001). Based on the results, this study gives credence to T. diversifolia essential oils as viable antibacterial agents.